'Integrated Naturopathy and Yoga' reduces blood pressure and the need for medications among a cohort of hypertensive patients in South India: 3-months follow-up study. Issue 3 (December 2016) - Edla, Srinivas Reddy; Kumar, Ajay M.V.; Srinivas, Bairy; Raju, Manthena S.; Gupta, Vivek
Highlights: Integrated Naturopathy and Yoga consisting of natural vegetarian diet (no added salt, sugar and oil), yogic-exercises and patient education reduced blood pressure and need for medications among patients with hypertension in South India. Of 80 patients, 79 (99%) achieved target BP control (<140/90 mmHg) and 66 (83%) achieved this with >50% reduction in antihypertensive medication dose at 3 months. In 8 (10%) patients, all medications were stopped while still maintaining normal blood pressure. There was a significant decrease in body weight, body fat and glycosylated haemoglobin (in diabetics). Abstract: Setting and objective: 'Manthena Satyanarayana Raju Arogyalayam' is a 500-bedded hospital in South India that offers 'Integrated Naturopathy and Yoga' (INY). Major components of INY package include an unrestricted diet of foods in natural form, daily yogic exercises, meditation for relaxation, patient counselling and health education in a highly structured routine for 15 days. We aimed to determine if INY reduced blood pressure and the need of anti-hypertensive medications in hypertensive patients. Design: Observational cohort study involving pre–post-comparative analysis of patients enrolled between April and July 2015. Blood pressure, anthropometry, blood parameters and compliance to diet and yoga (diet and yoga score on a scale of 0–10) were measured at baseline and 3 months. Results: Of 104 patients, 80 (77%) had 3-month follow-up. Of them, 79 (99%) achieved target BP control (<140/90 mmHg) and 66 (83%) achieved this with >50% reduction in antihypertensive medication dose, and in 8 (10%) patients, all medications were withdrawn. There was a significant increase in diet (2.7–7.4), yoga scores (1.5–5.6) and decrease in body weight, body fat, blood triglycerides and glycosylated haemoglobin levels. Conclusion: These early results are promising and need further study with long-term follow-up.